Recreational fishing along the Middle and Eastern Black Sea Turkish coasts : biological, social and economic aspects - Tunca, Sezgin (Array, 2018)
This study investigated biological, social and mainly economic dimensions of recreational fishing (RF) in 8 coastal Middle and Eastern Black Sea provinces of Turkey. In all provinces, a total number of 874 shore-based recreational fishers were interviewed via on-site face-to-face interviews during the fishing activity or at access points being monthly from January to December in 2015. Market value with RF index of added value approaches were used to calculate economic gains and losses from RF. The consistency was observed with the high education levels, high expense and high market value for fishers in the Middle Black Sea provinces; Kastamonu, Samsun, Sinop and Ordu. In all provinces, the harvesting costs stayed far below the average market prices of target species. Also, positive values of RF index were observed in all provinces. The species catch composition in Western and Eastern provinces did not show great differences. Furthermore, even if the habitat type along the Black Sea coast of Turkey did not show great variations, in the Western provinces some certain species including T. trachurus, S. sarda, B. belone, P. saltatrix, M. cephalus were caught in higher amounts. To summarize, RF along the Black Sea coasts of Turkey is an industry creating high economic returns by expenditures, jobs, catch value and further increased indirect economic impact in services sector.